a) D ∈ f(x) ⇔ f(4) = -1 ⇒ 4a -5 = - 1 4a =4 a = 1 f(x) = x -5
D ∈ g(x) ⇔ g(4) = - 1 ⇒ -4 +b = - 1 b = 3 g(x) = -x + 3
b) ptr. f(x) : intersectia cu OY x=0 f(0) = - 5 B(0 ,-5) = AB∧OY
intersectia cu OX: f(x) = 0 x-5 = 0 x = 5 A(5,0) = AB∧OX AB = graficul f(x)
ptr. g(x) : intersectia cu OY: x = 0 g(0) = 3 E(0, 3) = CE ∧ OY
intersectia cu OX: g(x) = 0 -x +3 = 0 x = 3 C(3, 0) = CE ∧ OX CE = graficul g(x)
EC ∧ AB
in Δ BDE se duce DD' _|_ BE
in ΔBOD BD² = OB² + OD² ⇒ BD = 4√2
in Δ DOE DE² = OD² +OE² ⇒ DE = 4√2
in Δ BDE BE² = BD² + DE² ⇒ Δ BDE = Δdreptunghic ⇒ ED_|_BD (EC_|_AB)